Open strategy mastering disruption from outside the C-suite - Stadler, Christian (Cambridge The Mit Press, 2021)
Why are some of the world's most successful companies able to stay ahead of disruption, adopting and implementing innovative strategies, while others struggle? It's not because they hire a new CEO or expensive consultants but rather because these pioneering companies have adopted a new way of strategizing. Instead of keeping strategic deliberations within the C-Suite, they open up strategic initiatives to a diverse group of stakeholders--front-line employees, experts, suppliers, customers, entrepreneurs, and even competitors. Open Strategy presents a new philosophy, key tools, step-by-step advice, and fascinating case studies--from companies that range from Barclays to Adidas--to guide business leaders in this groundbreaking approach to strategy. The authors--business-strategy experts from both academia and management consulting--introduce tools for each of the three stages of strategy-making: idea generation, plan formulation, and implementation. These are digital tools (including strategy contests), which allow the widest participation; hybrid digital/in-person tools (including a "nightmare competitor challenge"); a workshop tool that gamifies the business model development process; and tools that help companies implement and sustain open strategy efforts. Open strategy has an astonishing track record: a survey of 200 business leaders shows that although open-strategy techniques were deployed for only 30 percent of their initiatives, those same initiatives generated 50 percent of their revenues and profits. This book offers a roadmap for this kind of success.
Includes bibliographical references and index.
Keywords: Strategic planning